Health effects and complaints among sample residents who live close to petroleum plants in El Brega, Libya - Gadalla, Salah; Hamad, Wafa; Abdelwahab, Samah; Muhammed, Asma; Muhammed, Dalal (Libyan Journal of Science &Technology, 2022)
Petroleum emissions from refineries include a variety of metals and many types of gases which are recognized as carcinogenic and which cause adverse health problems as well. For many years, residents of rural areas who live in proximity to petroleum plants in some countries have complained of adverse health problems, which linked with gas emissions from nearby natural gas refineries. The aim of the study to know the percentage of health complaints and acute symptoms among residents sample. The study made on a random simple sample of residents who live close to petroleum plants in El Brega city. The data were collected from members of residents by using self-administered questionnaire which including questions on demographic and generic health and the health problems they may have. The results showed a high percentage of acute respiratory symptoms in the age group 45-65 years especially respiratory symptoms including a cough, wheezing, and difficulty in breathing with a percentage of 58% of participants. Participants who aged from 30 to 44 years is most likely are suffering from dermal reactions with a moderately high percentage, which is 61.5%. Conclusion: Our study showed excess in the prevalence of many acute respiratory health problems and complaints from petroleum emissions among members of the samples of residents.